Criminal Discomfort in Tourist and Recreational Areas of the Crimea-Caucasus Coast of the Black Sea: Geographical Aspect - Voronin, N.; A. Volkhin, Denis; A. Ozhegova, Lyudmila; Yu. Sikach, Kseniya; B. Shvets, Alexandra (Opción, 2019)
The article studies factors of formation of criminal phenomena that create an uncomfortable background of leisure activities in the areas of mass tourism and recreation on the Crimea-Caucasus coast of the Black Sea. The regional specificity of criminal discomfort in the studied segment of the Black Sea region is defined, as well as the degree of manifestation of criminal behavior on the Crimean-Caucasian coast of the Black Sea is investigated. The article studies the influence of the mechanism of recreational function of the Crimea-Caucasus Black Sea region on the process of antisocial phenomena formation within its territory, as well as reveals the possibilities of regula- tion of criminal behavior manifestation level in tourist and recreational areas of the Crimea-Caucasus coast of the Black Sea. The article determines the role of mass media in the formation of criminal-image characteristics of the territory of the Crimea-Caucasus coast of the Black Sea, influencing the preferences of potential tourists. The research methodology is applicable to other tourist and recreational areas. On its basis, it is possible to study the influence of urban, industrial, and rural functions of the territory on the formation of antisocial phenomena.